2017
DOI: 10.3390/ijerph14040416
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Pattern and Risk Factor Analysis of Hand, Foot and Mouth Disease Associated with Under-Five Morbidity in the Beijing–Tianjin–Hebei Region of China

Abstract: Hand, foot and mouth disease (HFMD) in children under the age of five is a major public health issue in China. Beijing–Tianjin–Hebei is the largest urban agglomeration in northern China. The present study aimed to analyze the epidemiological features of HFMD, reveal spatial clusters, and detect risk factors in this region. Reports of HFMD cases in Beijing–Tianjin–Hebei from 1 January 2013 to 31 December 2013 were collected from 211 counties or municipal districts. First, the epidemiological features were explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 34 publications
(61 reference statements)
6
37
0
1
Order By: Relevance
“…The results revealed that high-risk area were mainly in large cities, such as Beijing, Tianjin, Shijiazhuang and their neighbouring areas. This finding was consistent with that reported in previous studies [3,19,35]. Deng et al found that cluster centres of HFMD were almost the same in the capital of Guangdong province in China as in neighbouring areas [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results revealed that high-risk area were mainly in large cities, such as Beijing, Tianjin, Shijiazhuang and their neighbouring areas. This finding was consistent with that reported in previous studies [3,19,35]. Deng et al found that cluster centres of HFMD were almost the same in the capital of Guangdong province in China as in neighbouring areas [19].…”
Section: Discussionsupporting
confidence: 92%
“…Liu found that a cluster centre in Shandong province in China varied in different years [35]. Xu found that high-risk areas were mainly located in regions with a high level of economic development and population density [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, GDM can not only quantitatively determine the relative importance of each driving factor both in spatial and temporal variation, but also address the joint effects of these factors on the spatio-temporal variation of PM 2.5 concentrations. Therefore, GDM has attracted wide attention of the application from various fields with proven advantages [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to interpret the transmission pattern of HFMD owing to the presence of nonstationarity and nonlinearity in incidence data. Several factors, including climatic and socio-economic factors, are found to influence the pattern of HFMD, which reflects complex interactions among these factors [13][14][15][16][17]. As a result, incidence data of HFMD show strong seasonality, oscillations, and changes in period over time.…”
Section: Introductionmentioning
confidence: 99%